THE TRANSLATION PROCESS AND TECHNIQUES OF INTELLECTUAL PROPERTY RIGHTS TERMS IN THE INDONESIA-UNITED ARAB EMIRATES COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IUAE-CEPA) - Putri Carbelani Azzahra; Bob Morisson Sigalingging; Rizky Arif Afandi (Prodi Sastra Inggris UKI, 2025)
The translation of Intellectual Property Rights (IPR) terms in international trade agreement documents is both interesting and challenging to analyze in translation studies, because translators must understand IPR concepts and convey these terms in the target language appropriately. This research aims to analyze the translation process applied and techniques contained in translating IPR terms in the Indonesia-United Arab Emirates Comprehensive Economic Partnership Agreement (IUAE-CEPA) document. The data in this study are analyzed qualitatively by using a process-oriented approach referring to Nida and Taber (1982), translation techniques were classified based on Molina and Albir (2002) theory to identify the techniques used in translating IPR terms from English to Indonesian. The researcher managed to collect 36 data, 23 in the form of words, 13 in phrases showing that there are five types of intellectual property rights, the dominant appearing are copyright and related rights. Based on the analysis, the results show that the most dominant technique is established equivalence.